Pemodelan Lokasi-Alokasi Terminal Bahan Baku untuk Meminimasi Total Biaya Rantai Pasok pada Industri Produk Jadi Rotan - Yuniaristanto .; Wahyudi Sutopo; Azizah Aisyati (Institute of Research and Community Outreach - Petra Christian University, 2010)
In Surakarta and its surroundings (Solo Raya), there exists more than 400 Small-Medium Enterprises (SMEs) that produce finished products of rattan. Due to the high procurement cost as total operational cost of raw rattan distribution network from the sources, e.g. Borneo and Celebes to the rattan industries, the competitiveness of their products is lower than products from other countries. Therefore, to overcome the problem, those costs should be reduced for example by aggregating the demand of rattan industries. This police needs to be supported by the warehouse for storing and distributing raw rattan. Hence, this research aims to develop a facility location-allocation model so that total supply chain costs, including raw rattan procurement costs as well as facilities opening and closing costs can be minimized. The location-allocation model will be presented in a mixed integer non-linear programming model and solved using MS-Excel Solver. The results are number and location of the warehouse along with the raw rattan allocation in the warehouse to ensure raw rattan supply for rattan industries.